Thin section magnetic resonance diffusion‐weighted imaging in the detection of acute infratentorial stroke. Issue 5 (21st June 2016) - Entwisle, Tom; Perchyonok, Yuliya; Fitt, Greg
Abstract: Introduction: Magnetic resonance diffusion‐weighted imaging (DWI) is the most accurate technique available for demonstrating acute infarction; however, false‐negative DWI is higher in the infratentorium due to the limited spatial resolution with conventional 5 mm DWI. The aim of this study was to compare 5 mm DWI with 3 mm DWI in the detection of acute infratentorial infarction. Methods: A 3 mm DWI sequence of the infratentorium was incorporated into the conventional MRI stroke protocol for the evaluation of patients with vertebrobasilar stroke‐like deficits. The 5 mm and 3 mm DWI sequences were assessed by two neuroradiologists who were blinded to the clinical findings. Sensitivity and specificity analysis was then performed against the final clinical diagnosis. Results: The sensitivity for detection of infratentorial infarction was 81.1% for 5 mm DWI and 94.6% for 3 mm DWI and the specificity was 100% for 5 mm DWI and 97.7% for 3‐mm DWI. The false‐negative rate in detection of infratentorial infarcts was 5.6% for the 5‐mm sequence and 1.6% for the 3‐mm sequence. The six 5‐mm DWI false‐negative cases (4.8%) were less than 9 mm in diameter (3–8 mm, average 4.67 mm) and located in the brainstem. This supports the hypothesis that small lesions may not be detected on 5 mm DWI due to partial volume averaging. Conclusion: Where there is clinical suspicion of infratentorial infarction, 3 mm DWI of the infratentorium adds sensitivity compared to 5 mm DWI with only a small reduction in specificity.